2021
DOI: 10.1111/inr.12667
|View full text |Cite
|
Sign up to set email alerts
|

Nurses' experience of caring for people living with HIV: a focused ethnography

Abstract: Background Healthcare providers have been found to have limited knowledge and skills in interacting with people living with HIV. These factors can adversely affect providers' practice, jeopardize their safety and compromise the care of the patients. Aims This study aimed to explore the experiences of Iranian nurses who were caring for patients with HIV. Methods A focused ethnography approach was used. Participants consisted of 12 nurses working in teaching hospitals affiliated to Urmia University of Medical Sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
2

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 29 publications
0
4
0
2
Order By: Relevance
“…The fear of being infected, which is one of the sub-themes of our study, shows the nurses' concern about getting infected, and they are more worried about transmitting it to others, especially their family members than they are worried about themselves. Mashallahi et al (24) found that the fear of getting sick and passing it on to others, especially family members, reduces the quality of care measures. This fear reduces the quality of care measures performed by them.…”
Section: Discussionmentioning
confidence: 99%
“…The fear of being infected, which is one of the sub-themes of our study, shows the nurses' concern about getting infected, and they are more worried about transmitting it to others, especially their family members than they are worried about themselves. Mashallahi et al (24) found that the fear of getting sick and passing it on to others, especially family members, reduces the quality of care measures. This fear reduces the quality of care measures performed by them.…”
Section: Discussionmentioning
confidence: 99%
“…Healthcare providers are generally concerned about occupational exposure while caring for PLHWAs, particularly fear of needlestick injuries, which also aligns with previous findings [ 40 , 41 ]. Mashallahi and her colleagues [ 15 ] also concluded that nurses in Ulmia are constantly afraid of being infected with viruses while caring for patients, which may make healthcare providers hesitant to engage in providing care to PLWHAs and refuse to provide care [ 42 ]. Furthermore, "sense of duty" emerged as another category from the transcripts, consistent with Karuppiah's [ 43 ] findings.…”
Section: Discussionmentioning
confidence: 99%
“…Internationally, studies have revealed that seminar and virtual patient simulation activity focusing on PLWHAs can positively impact nursing students' attitudes [ 13 , 14 ]. Although nursing education programs have made great efforts over the past decade, and the proportion of healthcare providers unwilling to take care of patients with AIDS has declined, nursing practitioners still feel fear and tend to keep a distance from PLWHAs [ 15 , 16 ]. The underlying reasons why HIV and AIDS care occurs in the context of unfavorable nursing attitudes deserve to be futher explored.…”
Section: Introductionmentioning
confidence: 99%
“…Pacienti, ki živijo s HIV-om, se vsakodnevno borijo proti stigmi in diskriminaciji, vsakodnevno doživljajo strahove, ne le v povezavi z njihovim zdravjem, temveč z njihovo družbeno sprejemljivostjo. Zdravstveni delavci predstavljajo ključno vlogo pri nudenju skrbi omenjenim pacientom in v boju proti stigmi (Leyva-Moral, Gómez-Ibáñez, San Rafael, Guevara-Vásquez, & Aguayo-González, 2021), vendar družbena stigma in diskriminacija okuženih s HIV-om in obolelih z AIDS-om pri zdravstvenih delavcih povečuje strah za izvajanje zdravstvene nege (Mashallahi, 2021).…”
Section: Uvodunclassified
“…Ustrezna izobraževanja in usposabljanja medicinskih sester lahko bistveno izboljšajo njihov odnos, čustva in samozavest pri zagotavljanju kakovostne oskrbe okuženim s HIVom in obolelim z AIDS-om. Napačne predstave o HIV/AIDS-u lahko vplivajo na stališča in prakse medicinskih sester (Mashallahi, 2021).…”
Section: Uvodunclassified